The EFL Students’ Anxiety in an Online Public Speaking Class at an Indonesian University - Annisa Indira Sulistyowati; Thomas Wahyu Prabowo Mukti (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2023)
One of the main challenges for English as Foreign Language (EFL) students in the public speaking class was Foreign Language Anxiety (FLA). Due to COVID-19, the public speaking class must be conducted online. This study aimed to examine the level of FLA in online public speaking classes and discovered the impacts on students' feelings upon joining the online public speaking class. This research used a quantitative research approach. The research was conducted in the online public speaking classes for fifth-semester students at Sanata Dharma University. The researchers took 50 students from the total population of 159 students in batch 2019. The level of FLA was investigated through the Modified Foreign Language Classroom Anxiety Scale (MFLCAS), and the impacts of FLA were explored using Modified Foreign Language Virtual Classroom Anxiety Scale (MFLVCAS). The results showed that students experienced a moderate level of FLA with a mean of 3,00 by three dimensions; Communication Apprehension (CA), Fear of Negative Evaluation (FNE), and Test Anxiety (TA). There were no adverse impacts from online public speaking classes related to FLVCAS. The online classroom setting did not bring another source of anxiety to the students.